Associations between patient experience and clinical outcomes in general mental health clinics: Findings from the veterans outcomes assessment survey. (January 2021) - Katz, Ira R.; Resnick, Sandra; Hoff, Rani
Highlights: Most patients beginning mental health care in VA report the experience of care was positive Problems with communication and perceived quality predict dropouts and poorer outcomes Evaluating patient experience and addressing problems may improve outcomes Abstract: For mental health, evidence linking the patients' experiences of care with treatment outcomes is limited. We report findings from the Veterans Outcome Assessment (VOA) survey of Veterans beginning treatment in Veterans Health Administration (VHA) mental health programs with follow-up after approximately 3 months. In addition to assessments of symptoms and functioning, it includes key components of the Experience of Care and Health Outcomes (ECHO) survey including patient reports of communication with clinicians and of the overall quality of mental health care. For Veterans treated in VHA general mental health clinics, significant associations between ratings of communication and quality at baseline, and both retention in treatment and patient-reported outcomes assessed at follow-up demonstrate that better patient experience predicts more favorable outcomes. Further research is necessary to determine whether including them in measurement-based care could improve outcomes by facilitating the early identification of problems in providing care.